Răspunsuri

2014-01-26T18:42:51+02:00
1.(   (\sqrt{7-x} )^{2}   =    1^{2}  => -x=1-7 => x=6
2. a) ( \sqrt{2+x})^{2} = x^{2} => 2+x- x^{2} =0 /*(-1) =>  x^{2} -x-2=0
Δ= b^{2} -4ac=> 1+8=> 9
 x_{1,2} = \frac{-b+- \sqrt{delta} }{2a} =>
 x_{1,2} = \frac{1+-3}{2} =>
 x_{1} =2 ;  x_{2} = -1
b)  \sqrt{3x ^{3} } =x => {3x^{3} } = x^{2} => 3x^{3} - x^{2} =0;
 x^{2} (3x-1)=0 => \left \{ {{ x_{1} =o} \atop { x_{2}= \frac{1}{3}  }} \right.
pai zimil
sunt la amandoua ecuati
diana si al 3 ecuatie
nul facusi
Le-am facut pe toate 3